A New Surface Plasmon Resonance Assay for In Vitro Screening of Mannose-Binding Lectin Inhibitors. (August 2016) - Stravalaci, Matteo; De Blasio, Daiana; Orsini, Franca; Perego, Carlo; Palmioli, Alessandro; Goti, Giulio; Bernardi, Anna; De Simoni, Maria-Grazia; Gobbi, Marco
Mannose-binding lectin (MBL) is a circulating protein that acts as a soluble pattern recognition molecule of the innate immunity. It binds to carbohydrate patterns on the surface of pathogens or of altered self-cells, with activation of the lectin pathway of the complement system. Recent evidence indicates that MBL contributes to the pathophysiology of ischemia-reperfusion injury and other conditions. Thus, MBL inhibitors offer promising therapeutic strategies, since they prevent the interaction of MBL with its target sugar arrays. We developed and characterized a novel assay based on surface plasmon resonance for in vitro screening of these compounds, which may be useful before the more expensive and time-consuming in vivo studies. The assay measures the inhibitor's ability to interfere with the binding of murine MBL-A or MBL-C, or of human recombinant MBL, to mannose residues immobilized on the sensor chip surface. We have applied the assay to measure the IC50 of synthetic glycodendrimers, two of them with neuroprotective properties in animal models of MBL-mediated injuries.